Calcium pyrophosphate dihydrate crystal deposition: a clinical and laboratory analysis of 91 Thai patients - Louthrenoo W. (2014)
The clinical features and laboratory findings of 91 Thai patients (33 males and 58 females) with CPPD crystal deposition disease were studied. Their average age was 71.54 years. Acute monoarthritis and oligoarthritis were the two most common forms of presentation and were seen in 89 per cent of cases. The knee, wrist and ankle were the three most common joints involved. Associated diseases were common and included hypertension (30 cases), renal insufficiency (23 cases), chronic obstructive pulmonary disease (17 cases), coronary heart disease (13 cases) and diabetes mellitus (12 cases). Eleven patients had malignancies. Five patients had concomitant gout and CPPD crystal deposition disease. The knee and the wrist were the two most common sites of chondrocalcinosis. Of 67 patients who had thyroid function tested, 2 had hyperthyroidism and 5 had hypothyroidism. Hypomagnesemia was seen in 19 per cent. None had hypercalcemia, hypophosphatasia, hemochromatosis or hyperparathyroidism. In contrast to the western series, acute arthritis in our series responded well to oral colchicine alone.